Impact of Endoscopic Surgical Skill Qualification on Laparoscopic Resections for Rectal Cancer in Japan: The EnSSURE Study - Nobuki Ichikawa, MD, PhD; Shigenori Homma, MD, PhD; Koya Hida, MD, PhD; Tomonori Akagi, MD, PhD; Yasuyuki Kamada, MD, PhD; Tomohiro Yamaguchi, MD, PhD; Masaaki Ito, MD, PhD; Fumio Ishida, MD, PhD; Jun Watanabe, MD, PhD; Daisuke Yamamoto, MD; Hiroaki Iijima, MPH, MSc; Shigeki Yamaguchi, MD, PhD; et al. (Annals of Surgery Open, 2022)
Objective:. This cohort study investigated short- and long-term postoperative outcomes of laparoscopic procedures for rectal cancer performed with versus without certified surgeons. Background:. In Japan, the Endoscopic Surgical Skill Qualification System (ESSQS) evaluates surgical skills deemed essential for laparoscopic surgery; however, it is unknown whether this certification contributes to procedural safety. Methods:. Outcomes of laparoscopic rectal resections for cStage II and III rectal cancer performed from 2014 to 2016 at 56 Japanese hospitals were retrospectively reviewed. The impact of having versus not having certified surgeons on postoperative complications and other short- and long-term outcomes were assessed. In cases with ESSQS-certified surgeons, surgeons attended surgery in the capacity of an operator, assistant, scope operator, or advisor. Results:. Overall, 3188 procedures were analyzed, with 2644 procedures performed with and 544 without ESSQS-certified surgeons. A multivariate logistic regression model showed that the adjusted odds ratio of postoperative complications after procedures performed with ESSQS-certified surgeons was 0.68 (95% confidence interval, 0.51–0.91; P = 0.009). The adjusted odds ratios for conversion and pathological R0 resection rates with ESSQS-certified surgeons were 0.20 (P < 0.001) and 2.10 (P = 0.04), respectively. Multiple linear regression analyses showed significantly shorter surgical duration and more harvested lymph nodes for operations performed with ESSQS-certified surgeons. Multivariate Cox regression showed that the adjusted hazard ratios for poor overall and recurrence-free survival after operations performed with ESSQS-certified surgeons were 0.88 (P = 0.35) and 1.04 (P = 0.71), respectively. Conclusions:. This study showed the superiority of the short-term postoperative results for laparoscopic rectal procedures performed with ESSQS-certified surgeons.